Assess the Suicide Knowledge among Medical Students of Peoples University of Medical & Health Sciences for Women, Nawabshah District Shaheed Benazirabad, Sindh, Pakistan (Medical Forum Monthly, 2022)
Objective: To analyze the level of knowledge among medical students of Peoples University of Medical & Health Sciences for Women (PUMHSW) Nawabshah, District Shaheed Benazirabad, Sindh, Pakistan.Study Design: Descriptive cross sectional studyPlace and Duration of Study: This study was conducted at the Peoples University of Medical and Health Sciences for Women Nawabshah, District Shaheed Benazirabad Sindh from June, 2021 to November, 2021.Materials and Methods: Three hundred and seventy seven students were taken part in this study. Only 3rd, 4th and 5th year students were included. A series of questions were asked for assessing the knowledge of suicide, their factors and how to manage.Results: All were belonged to female gender because university is only for female gender. There were 126 from 3rd year with 33.42%, 137 from 4th year with 36.33% and 114 from 5th year with 30.24%. One hundred and thirty seven said yes about to get training questions while 242 said no, 54 said yes about management training questions while 323 said no and 62 said about counseling training while 315 said no.Conclusion: A special workshop and symposium was also arranged to enhance the skills and knowledge among graduates. Further it was also noticed that no proper counseling sessions were arranged so another recommendation is to arrange the counseling session with patients and to create the awareness among the local community.